THE USE OF GROUP FACEBOOK TO SUPPORT STUDENTS’ SELF DIRECTED ONLINE LEARNING - Pebriana, Rina; Arifin, Zainal; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of this study to know how Group Facebook support students’ self directed learning especially through online way. Therefore, the proliferation of digital, social network sites and mobile technologies have created a culture which the youth as a student become the participant. It changes the way students’ communicate, interact each other and also the way of learning. Case study methodology also allows researcher to emphasize the context, specializes in deep data and thick description. From this perspective, Group Facebook is very support for students’ self directed learning especially in online environment or called Self Directed Online Learning. This is an analysis regarding the evidences particularly proved by the transcripts of students’ interview to show the activities in Group Facebook. This article reports that Group Facebook as one feature of the most popular social network site help students’ as a bridge of discussion, e-portfolio, discussion place, and a place to enhance the knowledge..   Key Words: Group Facebook, Self Directed Online Learning   Abstrak: Tujuan penelitian ini adalah untuk mengetahui bagaimana Group facebook membantu pembelajaran mandiri mahasiswa terutama melalui cara online. Oleh karena itu, pertunbuhan angka pada alat digital, situs jaringan sosial dan teknologi mobile telah menciptakan sebuah budaya dimana para kaum muda sebagai mahasiswa menjadi peserta. Hal ini mengubah cara mahasiswa berkomunikasi, berinteraksi satu sama lain dan juga cara belajar. Metode studi kasus juga memperbolehkan peneliti menekankan pada konteks terutama pada data yang mendalam dan penggambaran yang padat. Dari sudut pandang ini, Grup Facebook sangat membantu untuk pembelajaran mandiri mahasiswa terutama lingkungan online atau disebut Pembelajaran Mandiri Online. Ini adalah sebuah analisa mengenai bukti-bukti terutama yang dibuktikan dengan transkrip interview paa siswa untuk menunjukkan aktivitas-aktivitas di dalam Grup Facebook. Artikel ini melaporkan bahwa Grup Facebook sebagai salah satu fitur pada situs jaringan sosial paling terpopuler membantu para mahasiswa sebagai jembatan informasi, online portfolio, tempat diskusi dan sebagai sebuah tempat untuk meningkatkan pengetahuan.   Kata Kunci : Grup Facebook, Pembelajaran Mandiri Online